DETERMINAN TABUNGAN MUDHARABAH DI INDONESIA - Roikhan Moch Aziz; Siti Suharyanti (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2013)
The objective of this research to determine how the influence of macro variables were Profit Sharing Ratio (equivalent rate), Inflation, GDP, and SWBI against Mudharabah Savings at Islamic Banking in Indonesia. The data used in this research were data time series by using multiple regressions and analysis by Ordinary Least Squares. The results showed that simultaneously independent variables (Profit Sharing ratio, Inflation, GDP, and SWBI have significant influence the dependent variable (MudharabaH Savings) with probability 0.000000. End that partially independent variables (Inflation with probability 0.0013, GDP with probability 0.0000, and SWBI with probability 0.0000 have positively influence and significantly to dependent variable (Mudharabah Savings) in the Islamic Banking of Indonesia. While between the variable independent (Profit Sharing ratio) to dependent variable (Mudharabah Savings) have not significantly with probability 0.2040, in the Islamic Banking of IndonesiaDOI: 10.15408/sjie.v2i2.2425